Completion surgery after extracapsular dissection of low‐grade parotid gland malignant tumors. Issue 9 (5th July 2019) - Mantsopoulos, Konstantinos; Mueller, Sarina; Goncalves, Miguel; Koch, Michael; Iro, Heinrich
Abstract: Background: The aim of the study was to compare the oncological and functional outcome between extracapsular dissection and completion surgery on the one hand and sole extracapsular dissection on the other hand in small low‐grade malignant parotid tumors. Methods: The records of all patients treated for T1‐T2 low‐grade malignant tumors of the parotid gland primarily by means of extracapsular dissection between 2006 and 2015 were studied retrospectively. Results: Forty patients with T1‐T2 low‐grade parotid malignancies were detected. Our study showed outstanding oncological outcomes in both patient groups, the facial nerve function being significantly better after sole extracapsular dissection in the direct postoperative phase, with no differences between the groups in the long term. Conclusions: Our study showed very encouraging preliminary results following primary extracapsular dissection as the sole surgical therapy for carefully selected low‐stage, low‐grade, inferiorly located lesions in patients with high compliance.